x2 plus 6x-2 equal -2x2 plus x ..
=7x equal -3x2 ..
4x=2
x=2 answer ..
check it if u dont want to trust ..
Improved Answer:
x2+6x-2 = -2x2+x
x2+2x2+6x-x-2 = 0
3x2+5x-2 = 0
(3x-1)(x+2) = 0
x = 1/3 or x = -2
The answer can be checked by using the quadratic equation formula.
Chat with our AI personalities
x2 + x2 = 2x2
x2 + x2 = 2x2
10x2 - 56 = 88 - 6x2 : 10x2 + 6x2 = 88 + 56 : 16x2 = 144 : x2 = 9 : x = ± 3
x3 - 2x2 + x - 2 =(x - 2)(x2 + 1)
You can work this out with long division, by checking to see if (x2 - 1) is a factor of (2x4 + 4x3 - x2 + 4x - 3). It is. Unfortunately, the WikiAnswers system is somewhat limited in depicting things such as long division, so we won't be able to represent it here. In short though, (2x4 + 4x3 - x2 + 4x - 3) / (x2 + 1) is equal to 2x2 + 4x - 3. which means that: (x2 + 1) / (2x4 + 4x3 - x2 + 4x - 3) = (x2 + 1) / (x2 + 1)(2x2 + 4x - 3) = 1 / (2x2 + 4x - 3)